Financial development, human capital accumulation and economic growth: empirical evidence from the economic community of West African States - Abubakar , Abdulsalam; Kassim, Salina; Yusoff, Mohammed (Elsevier, 2015)
Recently, much attention is given to financial-growth nexus, but largely via the physical capital accumulation channel. This study differed by examining this nexus, via the human capital accumulation channel in the ECOWAS region. It employed panel cointegration approaches as well as the FMOLS, DOLS. The results revealed that bank private credit and domestic private credit contribute significantly to economic growth in the ECOWAS, both directly and through their influence on human capital accumulation. These results imply that providing access to credit to both enterprises and individuals, through appropriate financial policies, will encourage economic growth in the ECOWAS region.